Eastern European economies : a region in transition - Goncalves, Marcus; Smith, Erika Cornelius (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Nearly seven decades ago, six countries in Western Europe (Belgium, France, West Germany, Italy, Luxembourg, and the Netherlands) decided to take economic cooperation to the next level. The vision of the European Union (EU) founding states, epitomized by the Schuman Declaration in 1950, was to tie their economies--including the reemerging West German economy-- so closely together that war would become impossible. Europe will not be made all at once, or according to a single plan. It will be built through concrete achievements which first create a de facto solidarity--Robert Schuman. In 1973, Denmark, Ireland, and the United Kingdom joined what was then referred to as the "European Community." The 1970s were also a decade of deep social and political transformations in Greece, Portugal, and Spain, where military regimes and dictatorships were overthrown. Inspired by the prosperity and stability of the European Community, these countries joined the European project within 10 years, strengthening their emerging democracies. The countries benefited enormously from free trade and common economic policies, in particular structural funds designed to foster convergence by funding infrastructure and investments in poorer regions. This book examines how these larger trends were experienced in individual member states throughout the Eastern European states. This book also scans the regional block of Central and Eastern Europe (CEE), South East Europe (SEE), and the Commonwealth of Independent States (CIS), and the macroeconomic dynamics of these states and the EU.
1. The European context for integration and accession -- 2. The role of the European Union in Eastern European economies -- 3. Eastern Europe regional bloc: CEE and CIS -- 4. The economic impact of integration -- 5. Challenges for entering Eastern European markets -- 6. Political risk in Eastern Europe -- 7. Future considerations and challenges -- Appendix A. A brief scanning of the CEE countries -- Appendix B. A brief scanning of the CIS countries -- Endorsements -- References -- Index.
Includes bibliographical references (pages 287-311) and index.
Title from PDF title page (viewed on July 15, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: European Union -- Economic policy; Europe, Eastern -- Economic conditions -- 1989-; CEE; CIS; Eastern European Economies; EU; European Union; Eurozone; Maastricht Treaty; Schuman Declaration; SEE; Western Europe; Electronic books